CARIES STATUS EARLY CHILDHOOD CARIES IN INDONESIAN CHILDREN WITH SPECIAL NEEDS : Study In SDLB Central Java - Sandy Christiono; R Rama Putranto (Odonto : Dental Journal, 2015)
Background: The prevalence of ECC (Early Childhood Caries) is still problem in Indonesian, especially in children with special needs. Unstable economic development leads to a poorer economic situation and may have an impact on increasing the prevalence of ECC. This study aimed to investigate the Caries Status of ECC in children with special needs and its association with sociodemografi and parental socioeconomic circumstances in Semarang, Central Java, Indonesian.Method: This research was conducted in SDLB using questionnaire and Using World Health Organization for diagnosis of caries. Informed consent from parents was obtained. The study sample was 21 children aged 3-6 years which consisted of 12 boys and 9 girls. Data were tested by Spearman correlation. Result: The result showed that 85.7% of the children had ECC. The result also showed significant association between ECC in the child and the age of the mother (r= 0.453, p=0.018), education level of the mother (r=0.741, p=0.0001), social status (r=0.807, p=0.0061) and other income (r=0.527, p=0.050). Conclusion: The conclusion of this study is that there was a significant association between caries status of a young child and the age of the mother, the socio-economic status and other income.